Behavioural and psychological symptoms of dementia in Down syndrome: Early indicators of clinical Alzheimer's disease?. (December 2015) - Dekker, Alain D.; Strydom, André; Coppus, Antonia M.W.; Nizetic, Dean; Vermeiren, Yannick; Naudé, Petrus J.W.; Van Dam, Debby; Potier, Marie-Claude; Fortea, Juan; De Deyn, Peter P.
Abstract: Behavioural and Psychological Symptoms of Dementia (BPSD) are a core symptom of dementia and are associated with suffering, earlier institutionalization and accelerated cognitive decline for patients and increased caregiver burden. Despite the extremely high risk for Down syndrome (DS) individuals to develop dementia due to Alzheimer's disease (AD), BPSD have not been comprehensively assessed in the DS population. Due to the great variety of DS cohorts, diagnostic methodologies, sub-optimal scales, covariates and outcome measures, it is questionable whether BPSD have always been accurately assessed. However, accurate recognition of BPSD may increase awareness and understanding of these behavioural aberrations, thus enabling adaptive caregiving and, importantly, allowing for therapeutic interventions. Particular BPSD can be observed (long) before the clinical dementia diagnosis and could therefore serve as early indicators of those at risk, and provide a new, non-invasive way to monitor, or at least give an indication of, the complex progression to dementia in DS. Therefore, this review summarizes and evaluates the rather limited knowledge on BPSD in DS and highlights its importance and potential for daily clinical practice.